Cerebrospinal Fluid T-Regulatory Cells Recognize Borrelia Burgdorferi Napa in Chronic Lyme Borreliosis. (October 2013) - Amedei, A.; Codolo, G.; Ozolins, D.; Ballerini, C.; Biagioli, T.; Jaunalksne, I.; Zilevica, A.; D'Elios, S.; De Bernard, M.; D'Elios, M.M.
The NapA protein of B. burgdorferi is essential for the persistence of spirochetes in ticks. One of the most intriguing aspects of NapA is its potential to interfere with the host immune system. Here, we investigated the role of the acquired immune responses induced by NapA in the cerebrospinal fluids (CSF) of patients with chronic Lyme borreliosis. We evaluated the cytokine profile induced in microglia cells and CSF T cells following NapA stimulation. We report here that NapA induced a regulatory T (Treg) response in the CSF of patients with chronic Lyme borreliosis and it is able to expand this suppressive response by promoting the production of TGF-β and IL-10 by microglia cells. Collectively, these data strongly support a central role of NapA in promoting both Treg response and immune suppression in the CSF of patients with chronic Lyme borreliosis and suggest that NapA and the Treg pathway may represent novel therapeutic targets for the prevention and treatment of the disease.